Асортимент і якість м’яких розсільних сирів на ринку України - Рябченко, Наталія Олександрівна (My University, 2008)
Проаналізовано ринок м'яких розсільних сирів, його частка в загальному виробництві сирів. Представлено аналіз виробництва м'яких розсільних сирів та їх класифікація. Досліджено асортимент розсільних сирів, який складається в основному з імпортних розсільних сирів. In the article the data about the market of brine soft cheeses, the share of brine cheeses in the market among other cheeses; manufacture and classification of the cheeses. Assortment of soft brine cheeses have researched. Analysis of assortment of brine soft cheeses, which are sold in the market of the Ukraine dairy product, states that it is formed mainly off the import cheeses. Special attention is allotted to properties of soft brine cheeses such as organoleptic and physical and chemical properties of brine cheeses.
Keywords: розсільний сир; pickled cheese; асортимент; якість; assortment; quality; кафедра експертизи харчових продуктів